Prediction of incident dementia: impact of impairment in instrumental activities of daily living and mild cognitive impairment : results from the German study on ageing, cognition, and dementia in primary care patients - Luck, Tobias; Weyerer, Siegfried (American journal of geriatric psychiatry, 2013)
Objectives: There is an increasing call for a stronger consideration of impairment in instrumental activities of daily living (IADL) in the diagnostic criteria of Mild Cognitive Impairment (MCI) to improve the prediction of dementia. Thus, the aim of the study was to determine the predictive capability of MCI and IADL impairment for incident dementia. Design: Longitudinal cohort study with four assessments at 1.5-year intervals over a period of 4.5 years. Setting: Primary care medical record registry sample. Participants: As part of the German Study on Ageing, Cognition, and Dementia in Primary Care Patients, a sample of 3,327 patients from general practitioners, aged 75 years and older, was assessed. Measurements: The predictive capability of MCI and IADL impairment for incident dementia was analysed using receiver operating characteristics, Kaplan-Meier survival analyses, and Cox proportional hazards models. Results: MCI and IADL impairment were found to be significantly associated with higher conversion to, shorter time to, and better predictive power for future dementia. Regarding IADL, a significant impact was particularly found for impairment in responsibility for one's own medication, shopping, and housekeeping, and in the ability to use public transport. Conclusions: Combining MCI with IADL impairment significantly improves the prediction of future dementia. Even though information on a set of risk factors is required to achieve a predictive accuracy for dementia in subjects with MCI being clinically useful, IADL impairment should be a very important element of such a risk factor set.
Available online 24 January 2013
Gesehen am 28.06.2018